Towards an Information Model of Consistency Maintenance in Distributed Interactive Applications. (21st May 2008) - Zhang, Xin; Ward, Tomás E.; McLoone, Séamus
Abstract : A novel framework to model and explore predictive contract mechanisms in distributed interactive applications (DIAs) using information theory is proposed. In our model, the entity state update scheme is modelled as an information generation, encoding, and reconstruction process. Such a perspective facilitates a quantitative measurement of state fidelity loss as a result of the distribution protocol. Results from an experimental study on a first-person shooter game are used to illustrate the utility of this measurement process. We contend that our proposed model is a starting point to reframe and analyse consistency maintenance in DIAs as a problem in distributed interactive media compression.